Developing Creative Tiktok Videos For English Speaking Practice Based On Students’ Needs Analysis - B. Bram Perdana Putra Gultom; Grace Adira Putri Pasaribu; Ezra Rodearni Aritonang; Anggraini Thesisia Saragih; Khairul Azmi Siagian (Faculty of Tarbiyah nad Teacher Training, 2026)
This study aims to develop creative TikTok videos for English speaking practice based on students’ needs analysis. The research applied a Research and Development (R&D) design, involving 30 English major students and two English lecturers. The data were collected through questionnaires distributed via Google Forms. The needs analysis results revealed that students mainly need speaking skills for career preparation and academic purposes, with major difficulties in grammatical accuracy and spontaneous speaking. Based on these findings, several TikTok videos were developed, focusing on daily conversation, role play, and interactive dialogue with a short duration of approximately one minute. The developed videos were then evaluated through expert validation using a Likert-scale questionnaire. The results showed high feasibility scores of 94% and 98%, which fall into the “very feasible” category. This indicates that the developed TikTok videos are appropriate as a learning medium for supporting students’ speaking practice. However, this study is limited to the development and validation stages, and further research is recommended to test the effectiveness of the product in real classroom settings.